Human exposure pathways to poly- and perfluoroalkyl substances (PFAS) from indoor media: A systematic review protocol. (January 2021) - DeLuca, Nicole M.; Angrish, Michelle; Wilkins, Amina; Thayer, Kris; Cohen Hubal, Elaine A.
Highlights: Protocol adapts existing systematic review tools for exposure science questions. Synthesize evidence between indoor PFAS exposure pathways and serum PFAS levels. Explain variability in serum PFAS from sources other than drinking water and diet. Development of exposure pathway-specific search strings for literature filtering. Use of artificially intelligent screening softwares to reduce screening time. Abstract: Background: Human exposure to per- and polyfluoroalkyl substances (PFAS) has been primarily attributed to contaminated food and drinking water. However, additional PFAS exposure pathways have been raised by a limited number of studies reporting correlations between commercial and industrial products and PFAS levels in human media and biomonitoring. Systematic review (SR) methodologies have been widely used to evaluate similar questions using an unbiased approach in the fields of clinical medicine, epidemiology, and toxicology, but the deployment in exposure science is ongoing. Here we present a systematic review protocol that adapts existing systematic review methodologies and study evaluation tools to exposure science studies in order to investigate evidence for important PFAS exposure pathways from indoor media including consumer products, household articles, cleaning products, personal care products, plus indoor air and dust. Objectives: We will systematically review exposure science studies that present both PFAS concentrations from indoor exposure media and PFAS concentrations in blood serum or plasma. Exposure estimates will be synthesized from the evidence to answer the question, "For the general population, what effect does exposure from PFAS chemicals via indoor media have on blood, serum or plasma concentrations of PFAS?" We adapt existing systematic review methodologies and study evaluation tools from the U.S. EPA's Systematic Review Protocol for the PFBA, PFHxA, PFHxS, PFNA, and PFDA IRIS Assessments and the Navigation Guide for exposure science studies, as well as present innovative developments of exposure pathway-specific search strings for use in artificial intelligence screening software. Data Sources: We will search electronic databases for potentially relevant literature, including Web of Science, PubMed, and ProQuest. Literature search results will be stored in EPA's Health and Environmental Research Online (HERO) database. Study eligibility and criteria: Included studies will present exposure measures from indoor media including consumer products, household articles, cleaning products, personal care products, plus indoor air and dust, paired with PFAS concentrations in blood, serum or plasma from adults and/or children in the general population. We focus on a subset of PFAS chemicals including perfluorooctanoic acid (PFOA), perfluorooctanesulfonate (PFOS), perfluorobutanoic acid (PFBA), perfluorobutane sulfonate (PFBS), perfluorodecanoic acid (PFDA), perfluorohexanoic acid (PFHxA), perfluorohexanesulfonate (PFHxS), and perfluorononanoic acid (PFNA). Study appraisal and synthesis methods: Studies will be prefiltered at the title and abstract level using computationally intelligent search strings to expedite the screening process for reviewers. Two independent reviewers will screen the prefiltered studies against inclusion criteria at the title/abstract level and then full-text level, after which the reviewers will assess the studies' risk of bias using an approach modified from established systematic review tools for exposure studies. Exposure estimates will be calculated to investigate the proportion of blood, serum or plasma) PFAS concentrations that can be explained by exposure to PFAS in indoor media.